An Evaluation of an Aftermarket Local Exhaust Ventilation Device for Suppressing Respirable Dust and Respirable Crystalline Silica Dust from Powered Saws - Garcia, Alberto (J Occup Environ Hyg, 2014)
The objective of this study was to quantify the respirable dust and respirable silica exposures of roofing workers using an electric powered circular saw with an aftermarket local exhaust ventilation attachment to cut concrete roofing tiles. The study was conducted to determine whether the local exhaust ventilation attachment was able to control respirable dust and respirable silica exposure below occupational exposure limits. Time-integrated filter samples and direct reading respirable dust concentrations were evaluated. The local exhaust ventilation consisted of a shroud attached to the cutting plane of the saw; the shroud was then connected to a small electric axial fan, which is intended to collect dust at the point of generation. All sampling was conducted with the control in use. Roofers are defined as those individuals who solely lay tiles. Cutters/roofers are defined as those workers who operate the powered saw to cut tiles and also lay tiles. Respirable dust from this evaluation ranged from 0.13 to 6.59 milligrams per cubic meter (mg/m(3)) with a geometric mean of 0.38 mg/m(3) for roofers and from 0.45 to 3.82 mg/m(3) with a geometric mean of 1.84 mg/m(3) for cutters/roofers. Cutters/roofers usually handle areas close to crevices, edges, or tips of the roof whereas roofers handle areas where complete tiles can be placed. The respirable dust exposures for all cutters/roofers indicated concentrations exceeding the Occupational Safety and Health Administration’s (OSHA) permissible exposure limit (PEL) for respirable dust containing silica; it was also exceeded for some of the roofers. The respirable silica concentrations ranged from 0.04 to 0.15 mg/m(3) with an average of 0.09 mg/m(3) for roofers, and from 0.13 to 1.21 mg/m(3) with an average of 0.48 mg/m(3) for cutters/roofers. As with respirable dust, the respirable silica exposures to cutters/roofers were higher than the exposures for roofers.